2021
DOI: 10.1007/s11547-020-01312-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis in COVID-19 patients in general wards: prevalence and association with clinical and laboratory variables

Abstract: Background Preliminary reports suggest a hypercoagulable state in COVID-19. Deep vein thrombosis (DVT) is perceived as a frequent finding in hospitalized COVID-19 patients, but data describing the prevalence of DVT are lacking. Objectives We aimed to report the prevalence of DVT in COVID-19 patients in general wards, blinded to symptoms/signs of disease, using lower extremities duplex ultrasound (LEDUS) in random patients. We tested the association of DVT with clinical, laboratory and inflammatory markers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
(23 reference statements)
1
22
0
2
Order By: Relevance
“…Lower extremity thrombosis classification has been suggested by the DVT guidelines and is widely used in clinical practice, and this classification stratifies the DVT patients into four classes [9]. Regarding the class, the majority of the DVT patients were diagnosed as Class I, which was consistent with other published papers [9], [15], [24]. The greatest number of detected DVT cases was in calf veins, but because of later complications such as the post-thrombotic syndrome and the mortality of 27% in these patients, early diagnosis and treatment is obligatory [9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lower extremity thrombosis classification has been suggested by the DVT guidelines and is widely used in clinical practice, and this classification stratifies the DVT patients into four classes [9]. Regarding the class, the majority of the DVT patients were diagnosed as Class I, which was consistent with other published papers [9], [15], [24]. The greatest number of detected DVT cases was in calf veins, but because of later complications such as the post-thrombotic syndrome and the mortality of 27% in these patients, early diagnosis and treatment is obligatory [9].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies demonstrated a significant increase in D-dimer and fibrinogen levels [23] as well as CRP value [24], which reflected the hypercoagulability state. On the other hand, Motaganahalli et al proved that the value of CRP is not associated with DVT [25].…”
Section: Discussionmentioning
confidence: 99%
“…Each biomarker considered in the inflammation-based risk scoring system was independently assessed for thrombosis in patients with COVID-19. Indeed, C-reactive protein was in-dependently associated with the presence of a deep-vein thrombosis demonstrated by duplex ultrasound as well as a pulmonary embolism demonstrated by computed tomography pulmonary angiography [34,35]. Moreover, C-reactive protein levels may predict the occurrence of venous thromboembolism in critically ill COVID-19 patients admitted to the ICU with an AUC of 0.75; for comparison, the AUC of the D-dimer in this study was only 0.64 [36].…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasound (US) is an imaging tool is cheap, noninvasive, non-irradiating and, thus, repeatable, suitable for patient disease monitoring [22][23][24][25]. Contrast-Enhanced Ultrasound (CEUS) imaging is an improved ultrasound-based technology, assuming the injection into the blood of a specific contrast agent, consisting of gas filled microbubbles [22].…”
Section: Diagnostic Tools Ultrasoundmentioning
confidence: 99%